Education in a Democratic Society: A Methodological Classic for Teachers and Students - Eche, Godwin A.; Ereba, Barida (NIU Journal of Social Sciences, 2020)
It is obvious that education thrives in an environment of freedom, which is democracy. Unfortunately, teachers sometime seem to treat students as passive recipients of knowledge. This trend makes students dummy learners, instead of making them construct their knowledge in interaction with the environment by reorganizing their mental structures. In that idyll, this paper, Education in a Democratic Society: A Methodological Classic for Teachers and Students is an apologia on the thrills of education in a democratic society. It encourages appropriate teaching methodology in a teaching/learning process. Understanding that holistic education undergoes the processes of policy enactment/implementation, administration, teaching and learning, with a constructivist mien, this paper x-rays the educational roles of teachers and students in a democratic society. Using constructive learning methodology, this paper emphasizes knowledge construction instead of knowledge acquisition. Keywords : Education, Democratic, Teachers, Students, Society